Bacteria in water - Rogers, Jessie Loyde (My University, 1904)
Introduction: Bacteriology is practically a new science and is one of utmost importance to each and every one of us, for our health alone. The science is only about twenty-five years old and at present is commanding the attention of the world in general. Bacteria, or worms, as they were then called were discovered several generations previous, but were not recognized then as now as forming a group by themselves. Instead, they were associated with a group of organisms including yeasts, molds, and microscopic animals. The science of bacteriology applies itself to almost every occupation and profession and for these reasons alone we should make a diligent and careful study of bacteria. We constantly come in contact with multitudes of these minute organisms and find them everywhere in external nature; in the soil, water, air, in the dust of the air and in out foods, and in the depths of the ocean, also on the skin of our bodies, in the mouth, respiratory passages and alimentary tract. They are less abundant, however, in mid ocean and at high altitudes. Very few are found at a depth of several feet in the ground. The economic considerations of bacteria in water is one of vita] importance. The health of a community depends largely on its water supply. If the water is contaminated by pathogenic bacteria disease and death are the results. While if the water is bacteriologically pure there are fewer diseases and less deaths from fevers etc. There are on record, numerous cases of outbreaks of typhoid fever and the causes have been traced to the contaminated water supply of the community. The typhoid bacillus is very frequently found in water and in the soil and as a result it may be carried to the source of the water used.
Citation: Rogers, Jessie Loyde. Bacteria in water. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Bacteria; Water; Water Quality; Theses